2020
DOI: 10.1021/acs.jpcc.0c05778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn and Ba Codoping on a Magnetic Spin Cycloid of Multiferroic Bismuth Ferrite Nanoparticles

Abstract: Bismuth ferrite (BFO) is the drosophila of research in multiferroic materials due to its simultaneous magnetic and electric ordering at room temperature. The unfortunate detail is its antiferromagnetic ordering, which practically cancels magnetization and magnetoelectric coupling of the crystals. To induce finite coupling, dopants have been introduced with a certain success so far. Nanoparticles (NPs) can additionally constrain the formation of the magnetic cycloid in BFO due to size confinement. Doping nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 80 publications
2
53
1
Order By: Relevance
“…Ba and Mn co-doped BFO NPs (Bi 1Àx Ba x Fe 0.95 Mn 0.05 O 3 : x ¼ 0.00, 0.01, 0.03, 0.05) were synthesized by a modied wet chemical 'sol-gel route' assisted by a calcination step at 773 K. 14 Bismuth nitrate Bi(NO 3 ) 3 $5H Photocatalysis (PC) procedure 10 À5 M of methyl orange (MO) and rhodamine B (RhB) aqueous suspensions were prepared. To establish an adsorptiondesorption equilibrium between the dye and the photocatalyst, 50 ml of organic dye with 0.025 g of NPs were placed into a jacketed beaker in the dark for 30 minutes.…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Ba and Mn co-doped BFO NPs (Bi 1Àx Ba x Fe 0.95 Mn 0.05 O 3 : x ¼ 0.00, 0.01, 0.03, 0.05) were synthesized by a modied wet chemical 'sol-gel route' assisted by a calcination step at 773 K. 14 Bismuth nitrate Bi(NO 3 ) 3 $5H Photocatalysis (PC) procedure 10 À5 M of methyl orange (MO) and rhodamine B (RhB) aqueous suspensions were prepared. To establish an adsorptiondesorption equilibrium between the dye and the photocatalyst, 50 ml of organic dye with 0.025 g of NPs were placed into a jacketed beaker in the dark for 30 minutes.…”
Section: Sample Preparationmentioning
confidence: 99%
“…11,12 BFO and doped BFO nanoparticles (NPs) are ferroelectric materials. 13,14 It has been shown that in photoferroelectric materials 15 the spatial separation of electrons (e À ) and holes (h + ) and their transfer from bulk to the surface is assisted by the presence of intrinsic spontaneous polarization induce local electric elds known as depolarization elds. 16 The role of this intrinsic electric eld for charge carrier dynamics in the ferroelectric photocatalyst for the photocatalytic redox reactions is fascinating, but the mechanisms are still not understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] Regarding chemical substitution, many studies have been carried out on the effect of codoping at both Bi and Fe sites on the ferroelectric and magnetic properties of BFO. [23][24][25][26][27][28] It is worth mentioning that La and Cr have usually been applied as dopants. Because of the differences in ion radius, substitution of La and Cr at Bi and Fe sites can lead to large lattice distortion, suppressing the spiral spin structure and inducing the FM phase in BFO.…”
Section: Introductionmentioning
confidence: 99%